2D Single‐Layer π‐Conjugated Nickel Bis(dithiolene) Complex: A Good‐Electron‐Poor‐Phonon Thermoelectric Material. (1st March 2019) - Deng, Tianqi; Yong, Xue; Shi, Wen; Gan, Chee Kwan; Li, Wu; Hippalgaonkar, Kedar; Zheng, Jin‐Cheng; Wang, Xiaobai; Yang, Shuo‐Wang; Wang, Jian‐Sheng; Wu, Gang
Abstract: Recently, the 2D d 8 planar π‐conjugated transition metal complexes have gained extensive attention owing to their extra‐high electrical conductivity. Meanwhile, low lattice thermal conductivities can be expected for their soft and microporous structures, suggesting very promising thermoelectric applications. Herein, based on first‐principles calculations and molecular dynamics simulations, it is identified that monolayered 2D nickel bis(dithiolene) complex, (NiC4 S4 ) n, is indeed such a material that exhibits exceptionally high electron mobility, low lattice thermal conductivity, and thereby excellent thermoelectric performance. The calculated figure of merit at 300 K can reach up to 0.92 for a perfect nanosheet. At the same time, the mechanism behind is uncovered, that is, the weak electron‐acoustic‐phonon coupling allowing high electron mobility, and its microporous structure decreasing the thermal transport. The surprisingly weak electron‐acoustic‐phonon coupling arises from mixed bonding–antibonding nature of conduction band. The finding opens a new opportunity for these 2D coordination complexes as potential thermoelectric materials. Abstract : High thermoelectric power factor and figure of merit zT are found in 2D nickel bis(dithiolene). The large carrier mobility and power factor come from weak electron‐acoustic‐phonon coupling arising from mixed bonding–antibonding nature of conduction band. Low lattice thermal conductivity due to its microporous crystal structure and complex phonon spectrum enhances its thermoelectric performance.